2019
DOI: 10.1016/j.meegid.2019.103967
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal survey of small mammal-borne Trypanosoma lewisi in Cotonou, Benin, and the potential risk of human infection

Abstract: Highlights-A qPCR-and 16SDNA sequencing-based search of Trypanosoma was conducted in 369 small mammals (i.e. 251 Rattus rattus, 18 R. norvegicus, 56 Mastomys natalensis, 2 Praomys derooi, 5 Cricetomys sp. and 37 Crocidura sp.) that were captured in three socio-environmentally degraded districts of Cotonou, Benin, during three different seasons of the same year.-Sequencing data allowed us to unambiguously identify Trypanosoma lewisi in 144 parasitized animals.-Prevalences were found to be very high with 57.2% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 37 publications
6
19
0
Order By: Relevance
“…The rodent species assemblage identified here in the commensal compartment of the Lake Nokoué ecosystem is quite similar to those observed in the urban and peri-urban areas of south Benin, including the lacustrine city of Ganvié (Hima et al 2019;Houéménou et al 2019). Such a small mammal community has already been associated with the circulation of various zoonotic agents in this area: Bartonella (Leulmi et al 2014;Martin-Alonso et al 2016), water-associated Leptospira (Houéménou et al 2019), Rickettsia (Leulmi et al 2014), and Trypanosoma (Dobigny et al 2019). The results obtained in the present manuscript showed that two species of rodents were found to harbor schistosomes: Rattus rattus and Mastomys natalensis.…”
Section: Discussionsupporting
confidence: 74%
“…The rodent species assemblage identified here in the commensal compartment of the Lake Nokoué ecosystem is quite similar to those observed in the urban and peri-urban areas of south Benin, including the lacustrine city of Ganvié (Hima et al 2019;Houéménou et al 2019). Such a small mammal community has already been associated with the circulation of various zoonotic agents in this area: Bartonella (Leulmi et al 2014;Martin-Alonso et al 2016), water-associated Leptospira (Houéménou et al 2019), Rickettsia (Leulmi et al 2014), and Trypanosoma (Dobigny et al 2019). The results obtained in the present manuscript showed that two species of rodents were found to harbor schistosomes: Rattus rattus and Mastomys natalensis.…”
Section: Discussionsupporting
confidence: 74%
“…In Senegal, a well-diversified bacterial community of 12 zoonotic OTUs (Operational Taxonomic Unit) was identified despite the Sahelian context and the use of different detection methods. The difference in the composition of these microparasitic communities shows the need to expand investigations to improve our knowledge of them, especially in Africa, where most studies focus on a single zoonotic agent [ 42 , 102 ], except when investigating the helminth community [ 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although Mello (1978) believed that there was a relationship of parasite–host specificity, it is currently known that T. Lewisi, although it has a higher rate of infection for Rattus rattus, is also capable of infecting several other wild rodent species [ 80 ]. The same has also been observed for primates [ 81 ], including man [ 82 ].…”
Section: Chagas Diseasementioning
confidence: 99%